Behavioral Dynamics of Farmers and First Buyer in Marketing Mangoes in Sedong District, Cirebon Regency, West Java - Aurelia Fadhilah Sari; Elly Rasmikayati; Bobby Rachmat Saefudin (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2019)
Mango marketing will be profitable for farmers if they are free to determine one of the first buyers in the market and get the maximum profit. But in reality, most mango farmers have a high dependence on selling their crops to middlemen. This is due to farmers' limitations on market information and access to capital. This research aimed at describe variation of first buyers for mango farmers and farmer's behavior in selling mango crops to first buyer parties. This research was conducted by survey research method. Respondents in this study were 50 mango farmers in Sedong District, Cirebon Regency. The data was analyzed using descriptive statistics and crosstabulation analysis. The results show that the variation of first buyers for mango farmers in Sedong District were a) 1 direction: wholesalers, middlemen/traders b) 2 directions: wholesalers, traditional markets; middlemen/traders, traditional markets; middlemen/traders, wholesalers, dan c) 3 directions: wholesalers, exporters, retailers; middlemen/traders, wholesalers, traditional markets. There are mango farmers who have sold to modern retailers, but have stopped doing partnerships because they are unable to fulfill the quality requirements set by modern retailers. However, majority of mango farmers (72%) in Sedong District still sell mango crops to middleman/traders.